2020
DOI: 10.3390/ijerph17228351
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Intensity and Player Duels in Under-13 Football Training in Switzerland

Abstract: We evaluated the structure (i.e., the different training parts), contents (i.e., the various activities used), intensity and occurrence of contact situations and headers during training sessions in under-13 football in Switzerland. A total of 242 players from 20 different teams on average aged 11.4 (SD 0.7) years participated. The participants were filmed during a typical training session while they were equipped with a heart rate sensor. The sessions were systematically recorded to allow for detailed analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(60 reference statements)
1
3
1
Order By: Relevance
“…Heading incidence in training of Under‐15 males is comparable to rates in the literature (IR: 2511) 16 . The number of headers per player per training in Under‐11 males, Under‐19 males, and Under‐17 females is similar to that of other observational studies with Under‐13 males, 19‐year‐old males (1 header per player per training), and Under‐16 females (approximately 1.4 headers per player per training) 26–28 . However, incidences in Under‐11 are much lower in the present study, compared to the Under‐12 in Beaudouin et al (IR: 5007) 16 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Heading incidence in training of Under‐15 males is comparable to rates in the literature (IR: 2511) 16 . The number of headers per player per training in Under‐11 males, Under‐19 males, and Under‐17 females is similar to that of other observational studies with Under‐13 males, 19‐year‐old males (1 header per player per training), and Under‐16 females (approximately 1.4 headers per player per training) 26–28 . However, incidences in Under‐11 are much lower in the present study, compared to the Under‐12 in Beaudouin et al (IR: 5007) 16 .…”
Section: Discussionsupporting
confidence: 82%
“…Despite canceled training sessions and matches due to pandemic situations, the number and exposure time of observed training sessions is much higher compared to previous studies 16,26,27,37 . Single training sessions showed at times very high heading exposures, due to sessions focusing on heading training.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…15 Whereas, it has been reported that 38% of training time in youth soccer practice is in situations where duels may occur, resulting in players being involved in one duel every 6.4 min. 16 Similarly, in adult football, it is estimated that 50% of all injuries are due to contact or foul play. 17,18 Although injuries resulting from contact cannot be prevented, research suggests that improving strength and stability will increase players' resilience to injuries across youth and adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Zen G has shown that the metabolic stress induced by 6 weeks of football training in the pre-match phase has a significant effect on the internal blood parameters of football players [3]. Experiments by Uebersax J assessed the structure, content, contact and intensity and incidence of headers in Swiss under-13 football training sessions [4]. Aleksieva M's research confirmed that after the game method was applied to football education, students' interest in football increased significantly [5].…”
Section: Related Workmentioning
confidence: 99%